The boredom in Kierkegaard and Heidegger - Cordeiro, Robson Costa (2021)
The article seeks to develop a phenomenology of boredom from Kierkegaard and Heidegger, starting mainly from an examination of the categories of possibility and instant and trying to see how these two categories converge in the thoughts of these two thinkers. In this way, boredom will be seen as the loss of the passion of possibility and as the refusal of the instant, aiming, with this, to establish a fundamental connection between boredom, the emptying of all meaning and time. The phenomenon of boredom will be examined neither as a psychological experience nor as something fortuitous or casual, but as a fundamental variation of anxiety, according to Kierkegaard, and as a fundamental mood disposition (Grundstimmung) of Dasein, according to Heidegger.